Relationship between Helicobacter pylori infection and celiac disease: a cross-sectional study and a brief review of the literature - Sebahat Basyigit; Oktay Unsal; Metin Uzman; Ferdane Sapmaz; Ozlem Ceylan Dogan; Ayse Kefeli; Zeliha Asilturk; Abdullah Ozgur Yeniova; Yasar Nazligul (Gastroenterology Review)
Introduction : Whether Helicobacter pylori triggers celiac disease (CD) or protects against CD is currently the subject of research. In the literature, there are epidemiologic studies that have reported conflicting results regarding the association between H. pylori and CD. Aim: To compare the prevalence of CD autoantibody positivity and the levels of CD autoantibodies between H. pylori -positive and H. pylori -negative subjects. Material and methods: This study was prospectively designed and included 240 dyspeptic patients who underwent upper gastrointestinal endoscopy with gastric and duodenal biopsies. The patients were divided into two groups according to presence of H. pylori infection. The serum levels of immunoglobulin (Ig) A, tissue transglutaminase antibodies (tTGA; IgA and IgG classes), and anti-endomysial antibodies (EMA; IgA and IgG classes) were measured for all participants by a blinded biochemistry expert. Results : There were no significant differences in the serum levels of CD autoantibodies or IgA between the two groups. There were also no significant differences in the percentages of subjects with positive CD serologies or subjects with IgA deficiencies between the groups. Conclusions : Helicobacter pylori remains one of the bacterial species that is most likely to trigger autoimmunity. However, studies have failed to reveal a relationship between H. pylori and CD; thus, additional basic work on the immunological aspects of the microbial-host interactions and longitudinal studies enrolling patients at very early stages of the disease may help us to address this issue.